2019
DOI: 10.1055/s-0039-1679893
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Dysfunction after Radiation for Anterior Skull Base Malignancies: Incidence and Screening

Abstract: Background Management of anterior cranial base malignancies requires multidisciplinary care. Radiation therapy remains a mainstay of definitive or adjuvant treatment. Apart from primary hypothyroidism, the effects of radiation on the hypothalamic–pituitary axis after high-dose treatment of head and neck malignancies remain poorly described. We describe a comprehensive screening protocol for surveillance and characterize the incidence of pituitary dysfunction after radiation for anterior cranial base malignanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…We found that the dose of skull base radiation (maximum dose to the primary tumor) did not significantly differ between the non-hypopituitarism and hypopituitarism groups (p 0.20). This seemingly contradicts the long standing existing literature 5,6,[28][29][30][31] that suggests a positive doseresponsive relationship between radiation dose and incidence of hypopituitarism, especially in the three axes we analyze in this study, although the data is mixed 29 . However, almost all of our patients received relatively high doses of radiation (average 71.4 gy) due to the aggressive nature of these tumors, which is well above the thresholds discussed for developing hypopituitarism.…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that the dose of skull base radiation (maximum dose to the primary tumor) did not significantly differ between the non-hypopituitarism and hypopituitarism groups (p 0.20). This seemingly contradicts the long standing existing literature 5,6,[28][29][30][31] that suggests a positive doseresponsive relationship between radiation dose and incidence of hypopituitarism, especially in the three axes we analyze in this study, although the data is mixed 29 . However, almost all of our patients received relatively high doses of radiation (average 71.4 gy) due to the aggressive nature of these tumors, which is well above the thresholds discussed for developing hypopituitarism.…”
Section: Accepted Manuscriptcontrasting
confidence: 99%
“…All rights reserved. from 37% over three years among our own institutional cohort of sinonasal malignancies 5 , to 41% at 6 years among adult survivors of nonpituitary brain tumors with radiation exposure 7 , and 82 8 -93% 9 for long-term survivors (greater than 10 years) of nasopharyngeal carcinoma. There is a well characterized dose-dependent sequence of pituitary derangements, with the somatotrophs more likely to be affected first at even low radiation doses; gonadal, adrenal, and thyroid axes are more likely to become dysfunctional with higher radiation doses and with increased time out from radiation 4,10 .…”
Section: Accepted Manuscriptmentioning
confidence: 81%
See 1 more Smart Citation
“…Hypopituitarism after radiation of nearby structures where the sella does not receive prescription dose is less well described. However, several series have shown that there is a linear dose response without a practical threshold, where increasing mean doses of radiation to the pituitary gland are more likely to cause hormone deficiencies [18][19][20]. As a result, the reduction in dose with the use of proton therapy seen in this study could be hypothesized to reduce the risk of hypopituitarism.…”
Section: Grade I Xerostomiamentioning
confidence: 80%
“…This is important because these high-grade cancers are more aggressive than other types of SNECs, and smCC has consistently been found to have lower survival than other types of SNEC. 5,[14][15][16][17] For these tumors, surgical resection may not be the ideal treatment. Not only can margins be difficult to clear, as they often extend well beyond gross tumor margins.…”
Section: Discussionmentioning
confidence: 99%